POETRY IS A MIRROR OF HAPPINESS. - Dilafruz Jabborova; Muyassar Mustafoyeva (Scholar Express Journal, 2022)
This article discusses the role of poetry in depicting the image of self aware people, a leading principle in the 80s short stories.
Keywords: landscape; monologue; detail; character